2017
DOI: 10.3390/rs10010028
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Organic Matter by VIS–NIR Spectroscopy Using Normalized Soil Moisture Index as a Proxy of Soil Moisture

Abstract: Soil organic matter (SOM) is an important parameter of soil fertility, and visible and near-infrared (VIS-NIR) spectroscopy combined with multivariate modeling techniques have provided new possibilities to estimate SOM. However, the spectral signal is strongly influenced by soil moisture (SM) in the field. Interest in using spectral classification to predict soils in the moist conditions to minimize the influence of SM is growing. The objective of this study was to investigate the transferability of two approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…The results from our study support their findings. Our previous study has showed that soil water had a nonlinear effect on reflectance spectra [5]. The wavebands after variable selection would definitely reduce the spectral variables involved in modeling, but these processes cannot change the nonlinear relation between soil water and reflectance spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from our study support their findings. Our previous study has showed that soil water had a nonlinear effect on reflectance spectra [5]. The wavebands after variable selection would definitely reduce the spectral variables involved in modeling, but these processes cannot change the nonlinear relation between soil water and reflectance spectra.…”
Section: Discussionmentioning
confidence: 99%
“…If the field/moist spectra can be directly applied to estimate SOM, then much of time and labor would be saved. However, the estimation of SOM with field/moist spectra may face some challenges: issues with field/moist spectra (e.g., soil particles, soil structure, soil surface and soil water content); difficulties in modeling a suitable VIS-NIR model due to the lack of available field/moist soil spectral libraries; unequal spectral responses in various soil types [4][5][6]. Variations from these factors (just mentioned above) might influence the model accuracy for SOM estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Since laboratory measurements are mainly conducted on air-dried and sieved soil samples, transferring such models to field conditions entails issues to be addressed, notably soil moisture that is known to affect the soils spectral signature [20,23,65,66]. Therefore, several studies have attempted to create prediction models for different levels of soil moisture [67][68][69]. The main absorption peaks of water content can be found near 1400, 1900, and 2200 nm due to the overtones and vibrations of the O-H group [70].…”
Section: Soil Moisture Effectsmentioning
confidence: 99%
“…In doing so, we ensured that the validation samples were evenly distributed in the range of the SOM concentration and covered the SOM diversity of expected future samples [44]. Moreover, such a division strategy was commonly adopted in previous studies using vis-NIR spectroscopy to estimate soil properties [27,38,61,62]. The raw spectra of the remaining 85 samples were pretreated by six methods, namely SG, FD, MC, log(1/R), MSC, and SNV.…”
Section: Inclusion Of Pretreatment In Sample Selectionmentioning
confidence: 99%